Low‐velocity impact response and compression after impact assessment of recycled carbon fiber‐reinforced polymer composites for future applications. Issue 8 (10th December 2013) - Shi, Jian; Bao, Limin; Kemmochi, Kiyoshi
<x xml:space="preserve">Abstract</x> The influence of recycling on the impact damage resistance of recycled carbon fiber‐reinforced polymer (CFRP) composites was investigated using low‐velocity impact and compression after impact (CAI) tests. The relationships among load, force, and time were analyzed to gain insight into the damage characteristics of three types of composite laminate: virgin CF‐reinforced polymer (V‐CFRP), recycled CF‐reinforced polymer (R‐CFRP), and treated recycled CF‐reinforced polymer (TR‐CFRP). Special emphasis was placed on evaluating the extent of damage and the residual mechanical properties as affected by three different fiber surface states. Substantial differences were noted in the shape, area, and damage mode of impact using ultrasonic c‐scanning, photography, and scanning electron microscopy (SEM). V‐CFRP indicated significant improvement in impact damage resistance in the form of less damage, higher residual strength, and greater shear failure angle. Damage resistance was improved up to 80% of V‐CFRP by surface cleaning while R‐CFRP is 50% of V‐CFRP. Shear failure angle of 16° was attained from R‐CFRP and it was increased to 24° when the recycled fibers were cleaned. The result of SEM showed that there was less delamination of TR‐CFRP compared with R‐CFRP. This work proves that the low‐velocity impact response of recycled composites can rival that of virgin composites, while providing a basis for future applications of recycled carbon in many fields. POLYM. COMPOS., 35:1494–1506, 2014. © 2013 Society of Plastics Engineers